Neurologically Compatible Digital Resources: Developing a Brain-Based Learning E-Book for an Introductory Nahw Course - Ahmad Zubaidi; Muhimmatul Mukaromah; Alvin Lailatul Maghfiroh; Muhammad Anwar Bin Ahmad (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This research aims to develop an introductory Arabic syntax (nahw) textbook integrating the Brain-Based Learning (BBL) approach and educational technology principles to enhance students’ syntactic competence and learning motivation in the Arabic Language Education Department at State Islamic University of Kiai Ageng Muhammad Besari, Ponorogo. Employing the Research and Development (R&D) methodology through the ADDIE model, data were collected using interviews, questionnaires, observations, and pre-/post-tests. Expert validation from material, media, and linguistics specialists confirmed that the textbook meets high-quality standards in content accuracy, visual layout, and cognitive-technological design. During implementation, classroom observations and assessments demonstrated significant improvements in students' understanding of basic syntax, practical rule application, and active participation. Statistical analysis using a paired-samples t-test indicated a significant improvement in the experimental group's scores from pre-test (M = 54,70, SD = 14,125) to post-test (M = 78,43, SD = 11,026). Furthermore, an independent samples t-test revealed that the experimental group significantly outperformed the control group (p = 0,023 < 0,05). These empirical learning gains were supported by positive student feedback regarding the textbook's readability and presentation. The evaluation confirms that blending BBL with modern educational technology tools successfully fosters neurologically compatible, interactive, and meaningful learning experiences. Consequently, the developed textbook is highly feasible, effective, and suitable as an innovative learning resource for undergraduate syntax instruction, serving as an essential reference for future digital textbook development.